Evaluación de la calidad en la microcuenca del río Bejuco mediante la aplicación de indicadores físico-químicos y microbiológicos - Reina Mora, Angélica María (2013)
This research determines the quality of the water in Bejucoriver by physical - chemical and microbiological indicators interrelated with the water quality index WQI and TULSMA to establish agricultural and domestic uses in dry and rainy seasons. It established three sampling stations including two points in each season and making two replicas in the dry and rainy seasons at each sampling point, in which analyzes physical, chemical and microbiological conditions, most of the results are within the maximum permissible limits of water for agricultural and domestic uses according to TULSMA. This followed the protocols established in Standard Methods, interrelated with the methodology of WQI. According to the range established was within 50-69 in the classification of water quality. Depending on its use as a general criterion is slightly contaminated, for public supply needs treatment, for recreation is acceptable but not recommended, for fishing and aquatic life is doubtful for sensitive species and for industrial and agricultural uses can be used untreated. Human activities that take place in its surroundings do not increased the incidence of contamination. We conclude that there is still a good way for aquatic life and the water in Bejucoriver can be used for any activity that is required.